Representasi Keanekaragaman Suku Bangsa Pada Tokoh Kartun Upin Ipin - Diamah Fitriyyah (UIN Sultan Maulana Hasanuddin Banten, 2023)
Ethnic diversity will exist in every country. Moreover, the country of Indonesia, which has many tribes, coupled with the inclusion of other ethnic groups, enriches diversity. Indonesia is experiencing a rift in harmony with respect to ethnicity. It is assumed that one ethnic group can dominate power in Indonesia. The broadcast of Upin Ipin's children teaches the next generation to respect other ethnic groups. The animated cartoons set an example for children to help each other and respect differences in friendship. Ethnic diversity is played by some of the cartoon characters. For example, the Indonesian ethnic group was represented by Susanti, the Indian nation was represented by Jarjit Singh, Rajoo, and Uncle Muthu, the Chinese were represented by the figures Meimei and Koh Ah Tong from the Chinese ethnic group, as well as the main character Upin Ipin and other figures representing the ethnic group. Malaysian nation. Described in the cartoon the characters help each other and respect each other even though they are of different ethnicities.